Lactobacillus rhamnosus improves feed intake, condition factors, hepatic and intestinal histomorphometric indexes of dourado Salminus brasiliensis - Oliveira, Fúlvia Cristina; de Almeida, Patrini Rodrigues; dos Santos Almeida, Rômullo Guilherme; Owatari, Marco Shizuo; Pilarski, Fabiana [UNESP]; dos Santos Fernandes, Carlos Eurico; de Campos, Cristiane Meldau (Springer Nature, 2024)
We herein investigated Lactobacillus rhamnosus as a probiotic, paraprobiotic and their synbiotic combination in the diet of dourado Salminus brasiliensis. Two hundred and forty juvenile S. brasiliensis with average weight and length of 6.78 ± 1.65 g and 8.97 ± 0.42 cm were randomly distributed in 16 experimental units (300 L) under four treatments: diet without additive (control), 0.02% probiotic (L. rhamnosus 108 CFU), 2.0% paraprobiotic (inactive L. rhamnosus 1010 CFU) and synbiotic (probiotic + paraprobiotic), all in quadruplicate, for 45 days. Then, zootechnical performance, hemato-biochemicals (pre-and post-challenge), intestinal and hepatic histomorphometric analyses were performed, in addition to a bacterial challenge with Aeromonas hydrophila. The feed intake was significantly lower (p < 0.05) in the probiotic group. The allomeric condition factors were significantly higher (p < 0.05) in fish from the paraprobiotic and synbiotic groups. No significant differences (p > 0.05) were observed in the blood count between the supplemented groups and the control group. However, significant differences (p < 0.05) were observed in the blood count between the pre- and post-challenge periods. Fish in the synbiotic groups had higher total villi height and villi height when compared to fish in the probiotic and control group. The serosa were significantly (p < 0.05) thicker in the intestines of fish from the probiotic and synbiotic groups. Goblet cells were significantly numerous (p < 0.05) in fish from the synbiotic group. In conclusion, the use of 0.02% probiotic, 2.0% paraprobiotic, and synbiotic proved to be a promising practice due to their action on productive performance, enabling weight gain similar to that of control group with lower feed intake. In addition to improving intestinal immune-histomosphometric parameters, possibly promoting an improved condition in facing intestinal pathogens.
Keywords: Fish farming; Functional diet; Lactobacilli-derived; Sustainability